THE MAIN TYPES OF COMPOUNDS USED AS CORROSION INHIBITORS ("Conference on Universal Science Research 2023", 2025)
Protection of metals against corrosion in different corrosive environments can be achieved using corrosion inhibitors, which are compounds added in small quantities to a corrosive solution to reduce or minimize the corrosion rate [1,2]. The economic impact of corrosion is substantial; for instance, according to international research by NACE (IMPACT 2016), the annual global economic damage due to corrosion amounts to approximately 2.5 trillion US dollars [3]. This represents about 3.4% of the average gross domestic product (GDP) of each country [4-6].